2018
DOI: 10.1038/s41598-018-19270-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards the scale-up of the formation of nanoparticles on α-Ag2WO4 with bactericidal properties by femtosecond laser irradiation

Abstract: In recent years, complex nanocomposites formed by Ag nanoparticles coupled to an α-Ag2WO4 semiconductor network have emerged as promising bactericides, where the semiconductor attracts bacterial agents and Ag nanoparticles neutralize them. However, the production rate of such materials has been limited to transmission electron microscope processing, making it difficult to cross the barrier from basic research to real applications. The interaction between pulsed laser radiation and α-Ag2WO4 has revealed a new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…This difference in morphology of Ag nanoparticles is caused by the differences in the formation process, leading to different time, temperature, and pressure conditions. For fs laser irradiation, the sample can reach a pressure of around 1010 Pa and a temperature of 1000 K, thus causing the formation of a large number of confined photons in a small area. Moreover, when irradiated with fs pulses, the sample is in the steady state, that is, it does not present vibrational and rotational movements, since these occur in the second peak scale, which makes it difficult to follow the dynamic process of particle nucleation …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference in morphology of Ag nanoparticles is caused by the differences in the formation process, leading to different time, temperature, and pressure conditions. For fs laser irradiation, the sample can reach a pressure of around 1010 Pa and a temperature of 1000 K, thus causing the formation of a large number of confined photons in a small area. Moreover, when irradiated with fs pulses, the sample is in the steady state, that is, it does not present vibrational and rotational movements, since these occur in the second peak scale, which makes it difficult to follow the dynamic process of particle nucleation …”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, it was observed that the results of the synthesized nanoparticles with these different laser parameters were similar. Previously, it was shown that the optimal conditions for the irradiation of semiconductors by femtosecond lasers result when the sample was irradiated with a mean power of 200 mW . Finally, to ensure that the pulse duration of the laser at the focal plane was 30 fs, a user‐adjustable postcompression stage, based on a pair of fused silica Brewster prisms, was employed to compensate for the dispersion in the beam delivery path.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group is engaged in a project devoted to study of the in situ nucleation and growth processes of Ag NPs on different Ag‐based semiconductors and Ag‐containing compounds, such as α‐Ag 2 WO 4 , β‐Ag 2 WO 4 , β‐Ag 2 MoO 4 , β‐AgVO 3 , Ag 2 CrO 4 , and Ag 3 PO 4 , with interesting technological applications such as photoluminescence, microbial agents, and photocatalysts . In this context, very recently, we have presented the scale‐up of the formation of Ag NPs on α‐Ag 2 WO 4 with bactericidal properties via fs laser irradiation . We have also recently presented the laser‐induced formation of Bi NPs with coexisting crystallographic structures (rhombohedral, monoclinic, and cubic) on NaBiO 3 with fundamental focus on laser‐based nanofabrication …”
Section: Qtaim Results Of the Charge Density ρBcp At The (3 −1) Bomentioning
confidence: 99%
“…The sample was placed on the bottom of a quartz cuvette and attached to a motion‐controlled 2D stage, moving at a constant speed of 0.45 mm s −1 at the focal plane perpendicular to the laser beam. The irradiation parameter values were selected based on previously reported experiments where the best NP growth in semiconductor networks was reported …”
Section: Methodsmentioning
confidence: 99%